(3EQTGO GdMceGAs - (3eQGO Hf jhSa LGhjT GdQhej Ke GdeUQj, GdeYQha HGdCRgQj,J (B1030 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ef fWaI Ke ef YdbI Ke ef eVZI aNdb s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3GdOfjG OGQ ef dG OGQ dg heGd ef dG eGd dg hdgG jLeY ef dG Ybd dg (B" (3aMjfFP hLH Ydi GdYGbd Cf jNJGQ GdBNQI , ceG bGd Gddg YR hLd (B:" (3hdbO hUjfG GdPjf ChJhG dGdcJGH ef bHdce (B" s
(3Vef eLehY s
(3LYdg ai (B87 (3aUdkGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B199 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B215s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B18 s
Keywords: (3GdWHs